The effect of ginseng (the genus panax) on glycemic control: a systematic review and meta-analysis of randomized controlled clinical trials. - Esra' Shishtar; John L Sievenpiper; Vladimir Djedovic; Adrian I Cozma; Vanessa Ha; Viranda H Jayalath; David J A Jenkins; Sonia Blanco Meija; Russell J de Souza; Elena Jovanovski; Vladimir Vuksan (PLoS ONE)
Importance Despite the widespread use of ginseng in the management of diabetes, supporting evidence of its anti-hyperglycemic efficacy is limited, necessitating the need for evidence-based recommendations for the potential inclusion of ginseng in diabetes management. Objective To elucidate the effect of ginseng on glycemic control in a systematic review and meta-analysis of randomized controlled trials in people with and without diabetes. Data sources MEDLINE, EMBASE, CINAHL and the Cochrane Library (through July 3, 2013). Study selection Randomized controlled trials ≥30 days assessing the glycemic effects of ginseng in people with and without diabetes. Data extraction Relevant data were extracted by 2 independent reviewers. Discrepancies were resolved by consensus. The Heyland Methodological Quality Score and the Cochrane risk of bias tool were used to assess study quality and risk of bias respectively. Data synthesis Sixteen trials were included, in which 16 fasting blood glucose (n = 770), 10 fasting plasma insulin (n = 349), 9 glycated hemoglobin (n = 264), and 7 homeostasis model assessment of insulin resistance (n = 305) comparisons were reported. Ginseng significantly reduced fasting blood glucose compared to control (MD =  -0.31 mmol/L [95% CI: -0.59 to -0.03], P = 0.03). Although there was no significant effect on fasting plasma insulin, glycated hemoglobin, or homeostasis model assessment of insulin resistance, a priori subgroup analyses did show significant reductions in glycated hemoglobin in parallel compared to crossover trials (MD = 0.22% [95%CI: 0.06 to 0.37], P = 0.01). Limitations Most trials were of short duration (67% trials<12wks), and included participants with a relatively good glycemic control (median HbA1c non-diabetes = 5.4% [2 trials]; median HbA1c diabetes = 7.1% [7 trials]). Conclusions Ginseng modestly yet significantly improved fasting blood glucose in people with and without diabetes. In order to address the uncertainty in our effect estimates and provide better assessments of ginseng's anti-diabetic efficacy, larger and longer randomized controlled trials using standardized ginseng preparations are warranted. Trial registration ClinicalTrials.gov NCT01841229.